Study of Brain Default Network Changes in Patients with Amnestic Mild Cognitive Impairment Based on rs-fMRI - HU Saiqin; Zhao Xv; Li Yaxue; Ji Yahong; LI Sha; LV Jing; ZHANG Yi; WANG Feng (康复学报)
ObjectiveTo explore the altered functional connectivity （FC） within default mode network （DMN） in patients with amnestic mild cognitive impairment （aMCI） and its relationship with cognitive function.MethodsAccording to the inclusion criteria and the exclusion criteria，resting-state functional magnetic resonance imaging （rs-fMRI） was performed on 40 untreated aMCI patients （aMCI group） and 40 volunteers （control group） with normal cognitive function. The gender，age，educationlevel of control group matched aMCI group. The DMN of 2 groups of subjects was extracted by independent component analysis （ICA）. The FC differences within DMN between 2 groups were comparied by SPM12 software. Pearson correlation or Spearman correlationof the zFC values of differential brain regions in aMCI groupwithneuropsychological scoreswas analyzed.ResultsCompared with control group，the FC enhanced brain regions in aMCI group：right parahippocampal gyrus，left insula，left posterior cingulate gyrus，left cuneus，right opercular part of inferior frontal gyrus，left superior margin gyrus，left precuneus and right precentral gyrus；The FC reduced brain regions：left middle frontal gyrus，right superior margin gyrus，right anterior cingulate gyrus，right angular gyrus and rightmiddle temporal gyrus. The correlation analysis showed that the zFC value in left middle frontal gyrus（r=0. 439，P=0. 005），rightmiddle temporal gyrus（r=0. 422，P=0. 007），right parahippocampal gyrus（r=0. 468，P=0. 002） and left precuneus（r=0. 482，P=0. 002）were positively correlated with MMSE score，and the zFC value in right anterior cingulate gyruswere positively correlated with AVLT-delayed recall score（r=0. 362，P=0. 022）and DST-forward score（r=0. 503，P=0. 001），while the zFC value in right precentral gyrus was negatively correlated with TMT-B score（r=-0. 450，P=0. 004）.ConclusionThe abnormal FC within DMN of patients with aMCI are associated with cognitive defect in memory，attention，executive functionand audio-visual function. It is speculated that FC changes within DMN may be an imaging biologic indicator for early recognition and diagnosisof AD.